DELVING THE HOOK SENTENCE IN ARGUMENTATIVE ESSAY: FINDING THE WRITERS’ PREFERENCES OF CATCHY SENTENCE - Yenni Arif Rahman (Universitas Majalengka, 2020)
Hook sentences as an opener and attention grabber in introductory paragraph play important role to make readers keep reading an essay. This means the structure and preferences to produce the hook is a key point to an interesting essay. The study aims to identify the writers’ preferences to write hook sentences. The data were 40 argumentative essays collected from 7 different international newspapers and gazettes. The study employs content analysis procedure to analyze 4 related categories to preferences: theme, number of words, types of sentence, and types of hooks. The subcategories which consist of 13 items is created to supply the detailed preferences. The result shows that all 40 samples utilize theme-related hook, with 34 (85%) samples written with more than 10 words, without dominant types of sentences (simple, compound, and complex), and with 23 (58%) narrative or story hook. From the result, it can be inferred that the writers prefer hook-related theme with mostly narrative type hook. The result also shows that there is relatively fair preference between simple and complex sentence use.